Tex. Penal Code arts. 611-12 (enacted Aug. 28, 1856), in 1 A DIGEST OF THE GENERAL STATUTE LAWS OF THE STATE OF TEXAS: TO WHICH ARE SUBJOINED THE REPEALED LAWS OF THE REPUBLIC AND STATE OF TEXAS (Williamson S. Oldham & George W. White, comp.) 458 (1859) - (:unkn) unknown (My University, 1859)
If one commits a killing with a Bowie-knife or dagger that would render a homicide manslaughter, that killing shall be deemed a murder.
Keywords: COMMITTING CRIME W/ WEAPON - NON-GUN ARMS